REKAYASA PENENTUAN JENIS KELAMIN DALAM KANDUNGAN MENURUT HUKUM ISLAM - Muh. Said HM (AHKAM : Jurnal Ilmu Syariah, 2014)
Engineering the Determination of Sex in the Womb According to Islamic Law. Currently, modern science and technology have developed quickly and dynamically. One development in medical science is engineering of the foetus (genetics) which can bring about benefits and at the same time possibilities that can be harmful to human dignity. Under Islamic law, engineering studies of the foetus can be categorised as a part of issues of fikih al-nawâzil. The problems are in need of the ihtiyâth ijtihâdiyyahprocess or regularity of istishlâhiyyah. Therefore, when mashlahahdominates as the main principle in engineering of the foetus then it can be justified. But if undertaken solely as a limited exercise at the same time determining the sex of the foetus then it cannot be justified under Islamic law because the exercise intervenes in the area of God Almighty in the creation of life.DOI: 10.15408/ajis.v14i2.1285